Splenium tracts of the corpus callosum degrade in old age. (18th January 2021) - Delvenne, Jean-Francois; Scally, Brian; Bunce, David; Burke, Melanie Rose
Highlights: Selective alterations in the splenium of the corpus callosum in old age. Splenium tracts that connect occipital areas are preserved in old age. Splenium tracts that connect parietal and temporal areas are impaired in old age. Abstract: It is well established that the posterior region of the corpus callosum, known as the splenium, is relatively preserved during the course of normal ageing. However, the effect of age on its distinct interhemispheric tract bundles that project to bilateral occipital, parietal and temporal areas of the cortex, is largely unknown. In the present study, diffusion tensor imaging was used to directly examine the integrity of these distinct segregations and their diffusion metrics were compared between groups of young adults (n = 20, mean age = 30.75) and older adults (n = 19, mean age = 80.21). Results revealed that while occipital tracts were preserved in older adults, parietal and temporal segments were particularly impaired. These findings are the first to indicate the existence of selective alterations in the posterior region of the corpus callosum in older age.